Pengaruh Digitalisasi, Keamanan Dokumen dan Efisiensi Kerja terhadap Kinerja Tata Kelola Dokumen - Joni Dwi Pribadi; Permanasari, Kartika Indah; Utaminingsih, Arni; Hadi, Musthofa; Fadilah, Zakiah Nur (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Document governance is an effort to organize documents well, neatly and systematically in accordance with applicable regulations and the needs of each organization. Good document governance can be seen from several perspectives, and this research uses digitalization, document security and work efficiency to measure it. This research uses an explanatory approach, which explores data by distributing questionnaires. Respondents in this research were alumni of the Department of Business Administration, Politeknik Negeri Malang, who had careers in government agencies, higher education institutions, state-owned enterprises and private companies who were members of the alumni group of the Department of Business Administration. Respondents were 86 people and were analyzed statistically using SEM PLS. The research results show that all the hypotheses developed were declared accepted, both for the direct relationship between digitalization, document security and work efficiency on document governance, as well as for the indirect relationship between digitalization on document governance and document security and work efficiency as the intervening.